Monitoring of polymer viscosity by simultaneous ultrasonic and rheological measurements at high and varying temperatures - Nesrine Houhat; Thibaut Devaux; Samuel Callé; Laksana Saengdee; Séverine Boucaud Gauchet; François Vander Meulen (AIP Advances)
A thorough comprehension of the rheological behavior of polymers during industrial processes is essential for optimizing manufacturing efficiency and product quality. The final properties and behavior of resulting polymer parts are known to be directly linked to the thermomechanical evolution of materials during their processing. The non-invasive monitoring of this stage could improve the quality of manufactured equipment. This can be done by tracking viscosity off-line on a rheometer. In this article, an experimental method to monitor the viscosity of polymer materials at high and varying temperatures by using ultrasound is proposed. This method allows us to measure the ultrasonic and rheological properties of a sample, simultaneously and in real-time. An ultrasonic instrumentation is adapted to a rheometer for continuous monitoring. It allows high-temperature range measurements (up to 200 °C). A dedicated signal processing algorithm is developed to determine the polymer longitudinal acoustic velocity by considering wave packet overlapping and temperature variation. Results on polyethylene show that ultrasonic parameters appear to be sensitive to changes in the polymer state. It enables more accurate detection of the onset of polymer crystallization. This study paves the way for ultrasonic real-time monitoring of the rotomolding process.